KEANEKARAGAMAN CAPUNG JARUM (ZYGOPTERA) DI TAMAN WISATA ALAM KERANDANGAN BATU LAYAR KABUPATEN LOMBOK BARAT - Lina Rahmawati; Siti Rabiatul Fajri; Sucika Armiani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2019)
Needle dragonflies are insects belonging to the Odonata order, sub-order Zygoptera. The purpose of the study was to determine the diversity of needle dragonfly and the type of needle dragonfly. This research was conducted in the Kerandangan Nature Tourism Park, West Lombok Regency in April 2019. This study used an entrapping or meshing method with a purposive sampling technique with sampling based on a consideration in which post 1 is a settlement and post 2 is a dense forest. The results showed that the needle dragonfly diversity index was categorized as being moderate in post 1 amounting to 1,220 and post 2 with a low category of 0,562.